The contribution of transaction costs to expected stock returns: A novel measure - Kazuhiro Hiraki; George Skiadopoulos (Queen Mary University of London, School of Economics and Finance, 2023)
We document that a theoretically founded, real-time, and easy-to-implement option-based measure, termed synthetic-stock difference (SSD), accurately estimates the part of stock's expected return arising from stock's transaction costs. We calculate SSD for U.S. optionable stocks. SSD can be more than 10% per annum, it can fluctuate significantly over time and its cross-sectional dispersion widens over market crises periods. We confirm the accuracy of SSD by empirically verifying the predictions of a general asset pricing setting with transaction costs. First, we document its predicted type of connection with various proxies of stocks' transaction costs. Second, we conduct simple asset pricing tests which render fur- ther support. Our setting allows explaining the size of alphas reported by previous literature on the predictive ability of deviations from put-call parity.
Keywords: C13; G10; G12; G13; 330; Transaction costs; Put-call parity; Return predictability; Informational content of options